Investigation of Novel Opuntia Ficus-indica Mucilage Nanofiber Membrane Filtration for Water Systems. Issue 1745 (9th June 2015) - Thomas, Sylvia W.; Devisetty, Manopriya; Katakam, Hruday Chand; Perez, Samuel; Guo, Fei; Stebbins, Daniela; Alcantar, Norma; Muppaneni, Rasudha
ABSTRACT: Nanofiltration technology is being investigated as a cost-eﬀective and environmentally acceptable mechanism of sustaining industrial and public water systems. Nanofiber membranes are part of the family of filtration devices being used to remove inorganics and organics from water systems. This study investigates the use of the natural material, Opuntia ficus-indica (Ofi) cactus mucilage, as a tool for nanofiber membrane filtration. Mucilage is a natural, non-toxic, bio-compatible, biodegradable, inexpensive and abundant material. Mucilage is a clear colorless substance comprised of proteins, mono-saccharides, and polysaccharides. It also contains organic species, which give it the capacity to interact with metals, cations and biological substances promoting flocculation for removing arsenic, bacteria, E. coli, and other particulates from drinking water. This natural material has the potential to be used as a sustainable method for water filtration and contaminant sensing. Therefore, mucilage nanofiber membranes were electrospun with volume ratios of polyvinyl alcohol (PVA) and polystyrene (PS) to mucilage comparing the interaction of non-polar solvents. Atomic Fluorescence Spectrometry (AFS) from PSAnalytical was used to evaluate electrospun nanofiber membranes made from volume ratios ranging from 30:70 to 70:30 of mucilage: polyvinyl alcohol, mucilage: polystyrene-D-limonene, and mucilage: polystyrene–toluene in different proportions. The mucilage nanofiber membranes were used as filtration devices for 50 ppb arsenic solutions. Arsenic, being a toxic substance, acts as a deadly poison in water systems and has plagued societal preservation for centuries. The total arsenic content in the samples were measured before and after treatment. Comparative tests were also performed using 1) coated and non-coated GVWP 0.22 µm and 0.45 µm filters from Millipore and 2) columnar flow through Pasteur glass pipets filled with 0.5 g of pre-washed sand from Fisher Scientific and 0.01 g of mucilage nanofibers. Results show mucilage: polystyrene nanofiber membrane filters were capable of removing arsenic from test solutions, in terms of the percentage of arsenic removed. These data elucidate that mucilage nanofiber membranes have the potential to serve as the basis for the next generation of economically sustainable filtration devices that make use of a natural non-toxic material for sustainable water systems.